Treatment of Odontogenic Cysts using a Minimally Invasive Approach: A Case Series from Vietnam - Luong, Minh Hang; Nhu Ngoc, Vo Truong; Cung, Tien Dat; Tran, Hau Bau; Luu, Quang Minh; Nguyen, Huu Huynh; Tran, Thao Phuong (UI Scholars Hub, 2024)
This study aims to evaluate the effectiveness of decompression as a treatment approach for radicular cysts in five pediatric patients. Case report: 5 pediatric patients with five cystic lesions from 6 to 11 years old diagnosed with radicular cysts were treated by decompression. Clinical and radiograph data from pre- and post-surgery were collected and analyzed. Complete resolution of all cystic lesions and simultaneous eruption of impacted teeth within the cyst were managed. The mean follow-up time is 25.6 months, and no recurrences were observed. Conclusion: Decompression should be considered a preferred treatment for cystic lesions in children, as it has the advantages of eliminating the development, reducing the extent of the cyst, stimulating bone healing, and facilitating the eruption of the permanent tooth germ.